2015
DOI: 10.1089/jpm.2015.29003.ka
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Candidiasis in Palliative Care Patients in Denmark

Abstract: In total, 52% of culture-positive patients harbored at least one isolate with innately or acquired decreased fluconazole susceptibility. Therefore, susceptibility testing appears recommendable for patients with clinical signs of OPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
7
2
1
Order By: Relevance
“…Com relação à candidíase oral, nesta pesquisa foi encontrado um percentual de 18%, o que corrobora a estimativa de 10% a 40% encontrada em outros estudos 27,28 , podendo chegar a 57% 3 . Em um estudo 29 no qual foi realizada a avaliação de 54 pacientes em um hospice da Dinamarca, 48% deles apresentaram sintomas clínicos de candidíase orofaríngea tratada inadequadamente quando admitidos no hospice, o que foi confirmado com a presença da forma de hifa na análise microscópica. Isto reforça que, quando essa infecção não é tratada de maneira adequada por um profissional capacitado, esses microrganismos podem exibir resistência intrínseca ou adquirida.…”
Section: Discussionunclassified
“…Com relação à candidíase oral, nesta pesquisa foi encontrado um percentual de 18%, o que corrobora a estimativa de 10% a 40% encontrada em outros estudos 27,28 , podendo chegar a 57% 3 . Em um estudo 29 no qual foi realizada a avaliação de 54 pacientes em um hospice da Dinamarca, 48% deles apresentaram sintomas clínicos de candidíase orofaríngea tratada inadequadamente quando admitidos no hospice, o que foi confirmado com a presença da forma de hifa na análise microscópica. Isto reforça que, quando essa infecção não é tratada de maneira adequada por um profissional capacitado, esses microrganismos podem exibir resistência intrínseca ou adquirida.…”
Section: Discussionunclassified
“…2 Palliative care patients admitted to a hospice in Denmark yielded a yeast carriage rate of 83%, where 48% had clinical signs of oropharyngeal candidiasis. 3 Another study found oral thrush in 47% of hospice patients. 4 Candida species are commensals in up to 40% of the healthy population but can be isolated from the mouth in more than 80% of patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Quelling the storm and restoring the oral biome supports the design of patient comfort. Candida should be cultured for sensitivity, evidenced by 52% of terminal patients in a Denmark study whom were colonized by a yeast with reduced susceptibility to Fluconazole(Astavad et al 2015). Patients with periodontal inflammation have shown recovery when treated with local culture supernatant Lacidophilus Strain (Haukioja, 2010).Probiotic engineering and local application show promise to aid in restoring oral biome in future.…”
mentioning
confidence: 99%